Czy zalegalizować narkotyki (wokół debaty amerykańskiej) - Krajewski, Krzysztof (Wydział Prawa i Administracji UAM, 1992)
The drugs legalization debate originated in the USA during the last decade, as current policies based on prohibition and broad criminalization became the target of increasing criticism, because of their ineffectiveness and many negative side effects. There is no doubt that proponents of such a move have many very strong and convincing arguments to support their position. But it is eually true that opponents are able to rise some very well grounded objections. The main Problem is, that both sides are unable to prove beyond any doubt their version of the consequences of abandoning prohibition, first of all with respect to eventual increases in the consumption of drugs. Because of this it seems that total legalization of all drugs may be currently too risky a step, Instead, an approach more permissive than current one should be recommended, first of all to avoid negative side effects of the strict prohibition so well described during the discussed here debate. This approach shall include experiments with step by step legalization of some drugs, first ofall soft ones. Also making possible legal access to drugs for the persons already addicted may be a wise step. Such approach was adopted vûth sucess by some European countries and should constitute the cornerstone of the drugs policies in Poland as well.
Should drugs be legalised? (on American debate)